2006
DOI: 10.1038/sj.bmt.1705455
|View full text |Cite
|
Sign up to set email alerts
|

Final height and gonad function after total body irradiation during childhood

Abstract: Short stature and gonad failure can be a side effect of total body irradiation (TBI). The purpose of the study was to evaluate the factors influencing final height and gonad function after TBI. Fifty young adults given TBI during childhood were included. Twenty-seven had been treated with growth hormone (GH). Those given single 10 Grays (Gy) or fractionated 12 Gy TBI had similar characteristics, GH peaks, final heights and gonad function. After the end of GH treatment, 11/20 patients evaluated had GH peak 410 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 24 publications
2
45
1
2
Order By: Relevance
“…in Leung et al 17 and þ 0.59Z in our study; (2) a maintained height s.d.s./Z-score 15,16,23 and (3) 'only' a height s.d.s./Z-score loss reduction. 1,2,24 In our study, the overall recovery effect from start of GH therapy to FH was stronger in girls. The similar pattern of recovery was observed by Dai 23 in a small series of seven patients.…”
Section: Response To Gh Treatmentmentioning
confidence: 64%
See 1 more Smart Citation
“…in Leung et al 17 and þ 0.59Z in our study; (2) a maintained height s.d.s./Z-score 15,16,23 and (3) 'only' a height s.d.s./Z-score loss reduction. 1,2,24 In our study, the overall recovery effect from start of GH therapy to FH was stronger in girls. The similar pattern of recovery was observed by Dai 23 in a small series of seven patients.…”
Section: Response To Gh Treatmentmentioning
confidence: 64%
“…ranged from À1.2 to À2 1,2,16,17,23,24 (Table 3). In our study height loss from AL diagnosis to GHD diagnosis was greater in girls and in patients younger than 5 years at the time of cranial irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated with TBI at a young age, and who have many years of linear growth ahead of them, are likely to suffer a greater height-loss than those treated at an older age; younger age at the time of SCT has, indeed, invariably been cited as a major risk factor for short stature in pediatric SCT recipients. 3,6,9,[22][23][24][25][26][27][28][29] The final height data reported by seven other studies are summarized in Table 4. 9,[22][23][24][25][26][27] In contrast to the studies by Bakker et al 22,26 and Cohen et al, 9 but in keeping with the findings of others, 23,25 we did not find a significant interaction between gender and final height.…”
Section: Discussionmentioning
confidence: 99%
“…We found that early HSCT significantly improved the height of patients in our population, in contrast to other non-MPS IH populations after HSCT. 22,23,34 Our patients were all young (0.5-3.7 years) at the time of HSCT, even so, we still found a greater impact on height for those who were transplanted at an older age, regardless of the age at last height evaluation. This effect is consistent with other studies of children with MPS IH, which also suggested improved outcomes for those children who were transplanted at a younger age.…”
Section: Discussionmentioning
confidence: 66%